Heroin dependence and HIV infection in Malaysia. - Chawarski, Marek C; Mazlan, Mahmud; Schottenfeld, Richard S (Drug and alcohol dependence, 2006)
Malaysia is experiencing severe problems with heroin dependence and HIV infection. This, study evaluated drug use and other HIV risk behaviors and their association with HIV and other infectious diseases in heroin-dependent subjects enrolled in a clinical trial of drug abuse treatment in Muar, Malaysia.
Keywords: Adult; Buprenorphine; Demography; Female; Heroin Dependence; HIV Infections; Humans; Malaysia; Male; Naltrexone; Narcotic Antagonists; Prevalence; Risk-Taking